澳門品德與公民教育校本課程初探 - Tchiang, I.; Ge, Yun (2nd Summit of Youth Education and Development in Hong Kong and Macau, 2020)

Parents, students and secondary schools in Macao - Tchiang, Van Man (University of Saint Joseph, 2009)
Macao, a developing city, has been undergoing rapid and significant changes economically, culturally, and socially, partly as a consequence of the changes to the economy brought about by the gaming and tourism industry. Changes in Macao have had a major impact on its schools. Parents have a significant impact on students in school, and Macao’s secondary schools are having to handle a range of challenges and problems brought by students and their parents, many of these as a result of the changes in the wider society of Macao. The response of many schools to the challenges faced is limited, and they understate and under-use the important role played by more developed forms of parental involvement in schools. This study examines the nature, scope and extent of the problems that secondary schools in Macao are having to handle from parents and students, how the schools are handling them, and what needs to be done in order to address the problems and handle them more effectively. Through a large scale survey, interviews and a small scale questionnaire, the thesis identifies key problems facing the schools from students and parents, and it reveals that many of Macao’s secondary schools are ill-equipped to handle these, and there are many signs that the problems are becoming more acute. The thesis finds that negative parental behavior has had a stronger effect on students than positive parental behavior, and it finds that there are several reasons why the schools, in their present state, cannot address these matters effectively. A significant gap is found between what the schools indicate they should be doing and what they are actually doing to address increased parental involvement in order to impact positively on Macao’s students. Recommendations are made for intervention and action
Keywords: PhD in Education (D-SE); Thesis and Dissertations; University of Saint Joseph